The Takht Eli Khanate: The State System at the Twilight of the Golden Horde - Vadim V. Trepavlov (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: The administrative structure of the Takht Eli (Great Horde) was inherited from the Jochi Ulus (the Golden Horde). However, the historical circumstances of the 15th century led to a simplification and contraction of the Takht Eli’s state apparatus, because the agricultural periphery of the Dnieper and the Northern Caucasus was too small to provide the economic foundation of the nomadic empire. The internal life of the Takht Eli was controlled by the administration of the khan's headquarters, as was typical for nomads in Eurasia. The main difference between the Takht Eli and the Golden Horde was the former’s lack of effective means of coercion to control disloyal subjects. With the almost complete loss of the agricultural foundation of the economy and without effective power structures, the khans of the Takht Eli found themselves leading a polity that could barely be considered a state. However, at the same time, the complex hierarchy of els and their leaders, the supra-tribal territorial division, and the remnants of the urban Islamic civilisation of the Golden Horde, especially in the Lower Volga, do not allow us to describe the Great Horde as a primitive social structure, such as a complex chiefdom. Perhaps, similar to the Uzbek khanate, the Great Horde can be defined as an inchoate state that occupied the intermediate stage between a complex chiefdom and a typical early state.